2011
DOI: 10.1371/journal.pone.0026315
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Impairs TLR9 Expression and Function in Plasmacytoid Dendritic Cells

Abstract: Plasmacytoid dendritic cells (pDCs) play a key role in detecting pathogens by producing large amounts of type I interferon (IFN) by sensing the presence of viral infections through the Toll-Like Receptor (TLR) pathway. TLR9 is a sensor of viral and bacterial DNA motifs and activates the IRF7 transcription factor which leads to type I IFN secretion by pDCs. However, during chronic hepatitis B virus (HBV) infection, pDCs display an impaired ability to secrete IFN-α following ex vivo stimulation with TLR9 ligands… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(156 citation statements)
references
References 45 publications
7
146
2
1
Order By: Relevance
“…39 Both hepatitis B and C viruses efficiently impair LR9 signaling in DCs and contribute to disease pathogenesis. 9,40 Recently, weak TLR response in HEV infection during pregnancy was reported; however, the study compared pregnant and nonpregnant women with HEV infection, but not those with or without liver failure. 41 This novel study is the first report showing the involvement of macrophages and TLR signaling defects in monocytes and macrophages in ALF patients during pregnancy (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…39 Both hepatitis B and C viruses efficiently impair LR9 signaling in DCs and contribute to disease pathogenesis. 9,40 Recently, weak TLR response in HEV infection during pregnancy was reported; however, the study compared pregnant and nonpregnant women with HEV infection, but not those with or without liver failure. 41 This novel study is the first report showing the involvement of macrophages and TLR signaling defects in monocytes and macrophages in ALF patients during pregnancy (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…There were significant differences in the ALT, aspartate aminotransferase (AST), bilirubin, and INR values in ALF-E(P) and in AVH-E(P) patients compared to HC(P) ( Table 1). All patients in the ALF-E(P) group were detected during late pregnancy in the third trimester (week 32; range, weeks [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. None of the AVH-E patients developed HE during the follow-up period.…”
Section: Alf-e Versus Avh-e Versus Healthy Pregnantmentioning
confidence: 99%
“…15 During chronic HBV infection, pDCs display reduced TLR9 expression and an impaired ability to secrete IFN-a after ex vivo stimulation with TLR9 ligands. 8,29,30 HBV virions were able to directly inhibit TLR9 transcription through downregulation of TLR9 promoter activity, by blocking the MyD88-IRAK4 axis and Sendai virus targeting IRF7 to suppress IFN-a production. 8 Along the same lines, Xu et al 31 demonstrated that HBsAg can inhibit TLR9-mediated IRF7 expression and nuclear translocation through upregulation of SOCS-1 expression.…”
Section: Interaction Between Tlrs and Hbvmentioning
confidence: 99%
“…Recent studies have indicated that TLR expression in peripheral immune cells, liver immune cells, and hepatocytes changed during chronic HBV infection accompanied by impaired TLR functions. [6][7][8][9] Meanwhile, TLR-mediated innate immune responses have been shown to inhibit HBV replication in hepatocytes and animal models. [10][11][12][13][14] Stimulation of innate immune responses with TLR agonists may further 1 improve the immunotherapeutic effect of combination strategies against the hepadnaviral infection.…”
Section: Introductionmentioning
confidence: 99%
“…15,[21][22][23]25 The mechanism of reduced IFN-a production remains to be determined. The downregulation of TLR-9 26 and interference with the mTOR pathway 21 have been suggested as potential mechanisms, but these studies were performed on healthy donor pDCs exposed to HBV in vitro. It seems unlikely that this effect would be directly modulated by the virus or viral antigens because four studies found no correlation between the viral load in patients and reduced IFN-a production by pDCs.…”
Section: Dendritic Cells In Chronic Hbv Aj Gehring and Ja D'angelomentioning
confidence: 99%